Model-based deployment of secure multi-cloud applications. (9th August 2019) - Casola, Valentina; Benedictis, Alessandra De; Rak, Massimiliano; Villano, Umberto; Rios, Erkuden; Rego, Angel; Capone, Giancarlo
The wide diffusion of cloud services, offering functionalities in different application domains and addressing different computing and storage needs, opens up the possibility of building multi-cloud applications relying upon heterogeneous services, offered by multiple cloud service providers. This flexibility not only enables an efficient usage of resources, but also allows to cope with specific requirements in terms of security and performance, while requiring, however, a typically high development effort. The MUSA framework leverages a DevOps approach to develop multi-cloud applications with desired Security Service Level Agreements (SSLA). This paper describes the MUSA Deployer models and tools, which aim at decoupling the multi-cloud application modelling and development from application deployment and cloud services provisioning. With MUSA tools, designers and developers are able to express and easily evaluate the application security requirements, and to deploy it automatically by acquiring and configuring cloud services with the needed software components.